Validation in the Development of Cost Accounting Practicum Module of Guided Discovery Methods - Susanti, Nora; Ramayani, Citra; Yulhendri, Yulhendri; Evanita, Susi (Fakultas Ekonomi, Universitas Negeri Semarang, 2019)
This study aims to validate the development of cost accounting practice modules so that they are more effectively used by students in the learning process. This type of research is descriptive research that will describe the validation process from module development to finding results about module validity that has been compiled. The source of research data was obtained from module validation sheets which were assessed based on each indicator by two experts. Data analysis techniques were carried out qualitatively and quantitatively. Data from the module validation sheet were analyzed quantitatively, and then descriptive techniques were used to draw qualitative conclusions. The results of the study indicated that the modules that have been designed were eligible to be used in the learning process of cost accounting practice courses at STKIP PGRI West Sumatra. These results were based on the results of material validation with an assessment of four indicators, namely the suitability of the material with competency standards, the accuracy of the material, supporting learning material and material updating with an average score of 3.2 by each expert. Expert advice for module improvement before practicing practice is that it is necessary to add information in the example of problem calculation and improvement in language writing.